2017
DOI: 10.3390/nano7120424
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Stretchable Strain Sensor Based on Ag@CNTs

Abstract: Due to the rapid development and superb performance of electronic skin, we propose a highly sensitive and stretchable temperature and strain sensor. Silver nanoparticles coated carbon nanowires (Ag@CNT) nanomaterials with different Ag concentrations were synthesized. After the morphology and components of the nanomaterials were demonstrated, the sensors composed of Polydimethylsiloxane (PDMS) and CNTs or Ag@CNTs were prepared via a simple template method. Then, the electronic properties and piezoresistive effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 29 publications
1
38
0
1
Order By: Relevance
“…In addition, an enhanced initial resistance and a non-linear response (sensitivity deviation) are always associated, increasing the need of the complicated calibration 28 . This may attributed to the release of strain energy via fracture of CNT junctions ensuing unsteady response [29][30][31][32] . The difficulty in fabrication of SWCNT based sensors of linear response emanated from ill contact between SWCNT owing to insufficient dispersion of SWCNT bundles in PDMS.…”
mentioning
confidence: 99%
“…In addition, an enhanced initial resistance and a non-linear response (sensitivity deviation) are always associated, increasing the need of the complicated calibration 28 . This may attributed to the release of strain energy via fracture of CNT junctions ensuing unsteady response [29][30][31][32] . The difficulty in fabrication of SWCNT based sensors of linear response emanated from ill contact between SWCNT owing to insufficient dispersion of SWCNT bundles in PDMS.…”
mentioning
confidence: 99%
“…For the special optical, thermal, catalytic, and electronic properties [1][2][3], one-dimensional (1D) metallic nanostructures have garnered a significant amount of research attention and found application in various devices [4,5]. For example, silver nanowires (AgNWs) have excellent electrical, transmittance, and flexible properties; also, the source of raw materials is wide and cheap [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Strains can be measured by sensors that rely on the piezoresistive effect [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the frequency shift of a resonator’s fundamental mode [ 34 , 35 , 36 ], the piezoelectric effect [ 37 , 38 ], the capacitance change [ 39 , 40 , 41 , 42 , 43 ], the optical properties changes [ 44 , 45 , 46 , 47 , 48 , 49 ], and other effects [ 50 , 51 , 52 ]. Piezoresistive effects consist of changes in the electrical resistance of a material when subjected to a mechanical strain.…”
Section: Introductionmentioning
confidence: 99%
“…Other strain sensors rely on the piezoresistive nature of carbon nanotubes that are dispersed in polymeric matrices, forming nanocomposites, and exhibiting a quasi-linear resistance change-strain response with gauge factors varying between −200 and 500 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. More recently, strain gauges using carbon nanotubes, graphene and other carbon nanomaterials are being developed and offer the promise of high gauge factors [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%